Times and experiences of a child in the context of Early Childhood Education (Práxis Educativa, 2025)
This article aims to analyze Carlos’s lived experiences (perizhivanya) within the social time of the Tupi Municipal Early Childhood Education School (EMEI Tupi, acronym in Portuguese) over three years, based on a dialogue among Philosophy, Sociology, Cultural-Historical Psychology, and Educational Ethnography. Drawing on participant observation, field diaries, and the viewing of video recordings from the three years of research, it is argued that the social times (chronological, aeonic, and kairotic) present in EMEI Tupi shape Carlos’s lived experiences, which in turn update, transform, and are transformed by the ways these times manifest themselves in the institutional daily life. In this sense, the institutional time is conceived as a totality in which the units [individual/collective], [regularity/singularity], and [evidencing/concealing] make visible the tensions of the regularity of chronological time and of human development. Thus, the institution’s routines cross and are crossed by Carlos’s singularity.Keywords: Time. Early Childhood Education. Perizhivanya.